An Observational Cohort Feasibility Study to Identify Microvesicle and Micro-RNA Biomarkers of Acute Kidney Injury Following Pediatric Cardiac Surgery. Issue 9 (September 2018) - Sullo, Nikol; Mariani, Silvia; JnTala, Maria; Kumar, Tracy; Woźniak, Marcin J.; Smallwood, Dawn; Pais, Paolo; Westrope, Claire; Lotto, Attilio; Murphy, Gavin J.
Abstract : Objectives: Micro-RNA, small noncoding RNA fragments involved in gene regulation, and microvesicles, membrane-bound particles less than 1 μm known to regulate cellular processes including responses to injury, may serve as disease-specific biomarkers of acute kidney injury. We evaluated the feasibility of measuring these signals as well as other known acute kidney injury biomarkers in a mixed pediatric cardiac surgery population. Design: Single center prospective cohort feasibility study. Setting: PICU. Patients: Twenty-four children (⩽ 17 yr) undergoing cardiac surgery with cardiopulmonary bypass without preexisting inflammatory state, acute kidney injury, or extracorporeal life support. Interventions: None. Measurements and Main Results: Acute kidney injury was defined according to modified Kidney Diseases Improving Global Outcomes criteria. Blood and urine samples were collected preoperatively and at 6–12 and 24 hours. Microvesicles derivation was assessed using flow cytometry and NanoSight analysis. Micro-RNAs were isolated from plasma and analyzed by microarray and quantitative real-time polymerase chain reaction. Data completeness for the primary outcomes was 100%. Patients with acute kidney injury ( n = 14/24) were younger, underwent longer cardiopulmonary bypass, and required greater inotrope support. Acute kidney injury subjects had different fractional content of platelets and endothelial-derived microvesicles before surgery. Platelets and endothelial microvesicles levels were higher in acute kidney injury patients. A number of micro-RNA species were differentially expressed in acute kidney injury patients. Pathway analysis of candidate target genes in the kidney suggested that the most often affected pathways were phosphatase and tensin homolog and signal transducer and activator of transcription 3 signaling. Conclusions: Microvesicles and micro-RNAs expression patterns in pediatric cardiac surgery patients can be measured in children and potentially serve as tools for stratification of patients at risk of acute kidney injury. Abstract : Supplemental Digital Content is available in the text.